2020
DOI: 10.1038/s41598-020-58861-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluopack screening platform for unbiased cellular phenotype profiling

Abstract: Beat nyfeler 2 & christophe Antczak 1* Gene and compound functions are often interrogated by perturbation. However, we have limited methods to capture associated phenotypes in an unbiased and holistic manner. Here, we describe Fluopack screening as a novel platform enabling the profiling of subcellular phenotypes associated with perturbation. Our approach leverages imaging of a panel of fluorescent chemical probes to survey cellular processes in an unbiased and high throughput fashion. Segmentation-free, whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…We then quantified this observation by measuring the area of individual droplets from a single imaging plane in at least 23 cells per clone and found that the average size of individual lipid droplets was up to 10 times larger among TMEM41B KO clones relative to wildtype cells ( Figure 4E ). Moretti et al reported a similar observation in TMEM41B KO H4 neuroglioma cells and it was later shown that these droplets contain neutral and sterol lipids ( Kang et al, 2020 ; Moretti et al, 2018 ).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…We then quantified this observation by measuring the area of individual droplets from a single imaging plane in at least 23 cells per clone and found that the average size of individual lipid droplets was up to 10 times larger among TMEM41B KO clones relative to wildtype cells ( Figure 4E ). Moretti et al reported a similar observation in TMEM41B KO H4 neuroglioma cells and it was later shown that these droplets contain neutral and sterol lipids ( Kang et al, 2020 ; Moretti et al, 2018 ).…”
Section: Resultsmentioning
confidence: 53%
“…To confirm these were indeed lipid droplets, we stained wildtype and six independent TMEM41B KO Huh-7.5 clones with Nile red and found that in all clones lipid droplets are considerably larger as compared to wildtype cells ( Figure 4D). We KO H4 neuroglioma cells and it was later shown that these droplets contain neutral and sterol lipids (Kang et al, 2020;Moretti et al, 2018).…”
Section: Tmem41b Snp Constructs Are Able To Maintain Normal Lipid Dismentioning
confidence: 99%
“… Moretti et al. (2018) reported a similar observation in TMEM41B KO H4 neuroglioma cells, and it was later shown that these droplets contain neutral and sterol lipids ( Kang et al., 2020 ).…”
Section: Resultsmentioning
confidence: 60%
“…Imaging mass cytometry also offers substantial multiplexing capacity, but requires expensive, slow instrumentation 175 , 176 . Multiplexed image profiles can also be created by combining readouts from multiple separate assays, each treated with a different fluorescent probe 177 , although preparing multiple wells per sample limits this approach to relatively small numbers of samples.…”
mentioning
confidence: 99%